2019
DOI: 10.1002/ghg.1875
|View full text |Cite
|
Sign up to set email alerts
|

Water–rock–CO2 interactions and CO2 storage of Honghe tight oil reservoirs: an experimental and simulation study

Abstract: CO2 flooding is essential for significantly enhancing oil recoveries and long‐term CO2 storage. We performed CO2 flooding experiments on target tight cores obtained from Honghe oilfield to investigate the water–rock interaction during CO2 flooding. In addition, we investigate the impact of mineralization and CO2 injection patterns on the sweep efficiency and CO2 long‐term storage using numerical simulations. Results show target core samples are composed of calcite, quartz, Na‐feldspar, and K‐feldspar. In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…After CO 2 is injected into a reservoir, it reacts with the formation water to form carbonic acid, which causes changes in pore structure. He et al [9] studied water-rock interaction in the CO 2 flooding process. They found that this interaction could reduce the permeability of natural fractures near the injection well, leading to improved CO 2 flooding efficiency in the fractured reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…After CO 2 is injected into a reservoir, it reacts with the formation water to form carbonic acid, which causes changes in pore structure. He et al [9] studied water-rock interaction in the CO 2 flooding process. They found that this interaction could reduce the permeability of natural fractures near the injection well, leading to improved CO 2 flooding efficiency in the fractured reservoirs.…”
Section: Introductionmentioning
confidence: 99%